A Model To Identify Factors Influencing Individual Phishing Susceptibility Among E-Mail Users - Allen, Anak Peter Diman (2023)
E-mail phishing is a serious problem for the human society as well as for the organisations. Previous studies have identified that an individual’s personality characteristics were among the key contributors to the problem. As such, this study has applied a combination of the Big-Five Personality Traits Theory, the Protection Motivation Theory, and Cialdini's Principle of Persuasion as its research model. The structural Equation Modelling (SEM) technique was used to measure hypothetical, direct, and mediated relationships between the constructs of the study. Data collection using survey questionnaires was collected from 403 respondents who use e-mails as part of their daily tasks. This study's findings revealed a relationship between individuals' personality traits and how they perceive themselves in appraising phishing threats and associated coping strategies. The study also found that individual levels of appraisal concerning the threat of phishing and coping strategies can affect their likelihood of becoming a phishing victim. Finally, the study discovered that the relationships between an individual’s personality traits and an individual’s phishing susceptibility can be further explained through the mediating effect of threat and coping appraisal. The primary contribution of this study lies in its novel approach of utilising the Protection Motivation Theory to explain the factors that render certain characteristics of individuals more vulnerable to phishing attacks as a result of their unique personality traits.